Kuwait : Selected Issues. (IMF Staff Country Reports; Country Report, 2014)
This Selected Issues paper discusses the designing and implementing of Kuwait's fiscal policy for the medium term. Fiscal policy has a major role to play in supporting macrostability and diversification. The fiscal strategy design and implementation on a yearly basis are based on a few key areas such as determining targets or ceilings for major fiscal parameters for a three-year rolling framework with binding next budget year and indicative two outer years, establishing a clear process for expressing policy objectives and their link to expenditure, et cetera The illustrative budget sequencing with the fiscal strategy spearheading medium-term fiscal policymaking and linked to the annual budget process would support fiscal policy implementation.